2014
DOI: 10.1186/1471-2164-15-153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of Al tolerance QTLs in the maize genome by high density SNP scan

Abstract: BackgroundAluminum (Al) toxicity is an important limitation to food security in tropical and subtropical regions. High Al saturation on acid soils limits root development, reducing water and nutrient uptake. In addition to naturally occurring acid soils, agricultural practices may decrease soil pH, leading to yield losses due to Al toxicity. Elucidating the genetic and molecular mechanisms underlying maize Al tolerance is expected to accelerate the development of Al-tolerant cultivars.ResultsFive genomic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 62 publications
4
39
0
1
Order By: Relevance
“…Similar results have recently been demonstrated in maize where ZmMATE1 expression, controlled either by three copies of the target gene or by an unknown molecular mechanism, is responsible for Al tolerance mediated by QTL mapped on chromosome 6 ( qALT6 ) (Guimaraes et al. ). Polymorphisms in regulatory regions of Alt(Sb) are likely to contribute to large allelic effects, acting to increase Alt(Sb) expression in the root apex of tolerant genotypes.…”
Section: Sorghum Tolerance To Aluminium Toxicitysupporting
confidence: 81%
“…Similar results have recently been demonstrated in maize where ZmMATE1 expression, controlled either by three copies of the target gene or by an unknown molecular mechanism, is responsible for Al tolerance mediated by QTL mapped on chromosome 6 ( qALT6 ) (Guimaraes et al. ). Polymorphisms in regulatory regions of Alt(Sb) are likely to contribute to large allelic effects, acting to increase Alt(Sb) expression in the root apex of tolerant genotypes.…”
Section: Sorghum Tolerance To Aluminium Toxicitysupporting
confidence: 81%
“…Similarly, aluminium tolerance conferred by chelating complexes of DIMBOA and Al (III) has been proposed [106]. However, recent studies using defined maize lines and BX-free mutants could not detect a significant correlation between BXs and Al (III) sensitivity [8,107,108].…”
Section: Benzoxazinoids In the Soil: Allelopathy And The Chelating Ofmentioning
confidence: 99%
“…Contrasts between root and shoot growth of the tolerant check, the Original cultivar (M 0 ) and selected mutant tef lines under unlimed, acid soil conditions. maize, exclusion and internal detoxification mechanisms controlled by several quantitative genes are involved in Altoxicity tolerance (Maron et al 2008(Maron et al , 2010Huang et al 2009Huang et al , 2012Yamaji et al 2009;Xia et al 2010Xia et al , 2011Yokosho et al 2011;Chen et al 2012;Guimaraes et al 2014). Comparative mapping study among important cereals crops indicated extensive synteny or colinearity of Al-tolerance loci among genomes of rice, wheat, barley, rye, oat, maize, and sorghum (Jardim, 2007).…”
Section: Discussionmentioning
confidence: 99%